2012
DOI: 10.1101/gad.207415.112
|View full text |Cite
|
Sign up to set email alerts
|

BAF60 A, B, and Cs of muscle determination and renewal

Abstract: Developmental biologists have defined many of the diffusible and transcription factors that control muscle differentiation, yet we still have only rudimentary knowledge of the mechanisms that dictate whether a myogenic progenitor cell forms muscle versus alternate lineages, including those that can be pathological in a state of disease or degeneration. Clues about the molecular basis for lineage determination in muscle progenitors are only now emerging from studies of chromatin modifications that avail myogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 108 publications
1
63
0
Order By: Relevance
“…Previous work demonstrated that the SWI/SNF subunit BAF60c is critical for both skeletal and cardiac myogenesis (Lickert et al 2004;Takeuchi and Bruneau 2009;Forcales et al 2011). Three Baf60 variants (Baf60a, Baf60b, and Baf60c) are incorporated into the SWI/SNF complex in a mutually exclusive manner that has been proposed to influence the selectivity of the complex for distinct sites in chromatin (Wu et al 2009;Puri and Mercola 2012). The upstream signaling that directs the relative expression of the Baf60 variants and their activity during cardiogenesis is unknown.…”
Section: Nodal and Bmp Inhibition Induce The Swi/snf Component Baf60cmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work demonstrated that the SWI/SNF subunit BAF60c is critical for both skeletal and cardiac myogenesis (Lickert et al 2004;Takeuchi and Bruneau 2009;Forcales et al 2011). Three Baf60 variants (Baf60a, Baf60b, and Baf60c) are incorporated into the SWI/SNF complex in a mutually exclusive manner that has been proposed to influence the selectivity of the complex for distinct sites in chromatin (Wu et al 2009;Puri and Mercola 2012). The upstream signaling that directs the relative expression of the Baf60 variants and their activity during cardiogenesis is unknown.…”
Section: Nodal and Bmp Inhibition Induce The Swi/snf Component Baf60cmentioning
confidence: 99%
“…In addition to the Brg1 or Brm catalytic proteins, SWI/SNF consists of 10-16 noncatalytic Brg1/Bafs in mammals, including the 60-kDa Baf60a, Baf60b, and Baf60c proteins (Albini and Puri 2010;Lessard and Crabtree 2010;Euskirchen et al 2012). An emerging concept is that lineage selectivity is based on the mutually exclusive, combinatorial assembly of variants of the Baf structural subunits into SWI/SNF (Wu et al 2009;Puri and Mercola 2012). The variant composition is thought to promote interactions with specific transcription factors that cause SWI/SNF to recognize discrete, lineage-appropriate sites in chromatin.…”
Section: A Chromatin Remodeling Model For Cardiomyogenic Commitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…SWI/SNF complex appears to mediate the unique ability of MyoD and Myf5 to remodel the chromatin and activate transcription at previously silent muscle loci [6,7], but is also required for the maintenance of muscle gene expression at later stages of skeletal myogenesis [8]. SWI/SNF complexes are composed of two mutually exclusive enzymatic subunits (the ATPases Brahma (Brm) and Brm-related gene 1 (Brg1)) and a number of structural subunits, collectively referred to as Brg1/Brm-associated factors (BAFs) [9,10]. Because of the variable, cell type-specific assembly of distinct subunits and their alternative variants, SWI/SNF complexes are heterogeneous in their composition and function [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The human accessory subunits BAF60a/SMARCD1, BAF60b/SMARCD2, and BAF60c/SMARCD3 and their worm homologs HAM-3 and SWSN-2.2 derive from the same evolutionary ancestor and are expected to belong to both subclasses of complexes (Shibata et al 2012;Weinberg et al 2013) (Figure S1 and Figure S2). The three human BAF60 proteins, which present 60% of similarity in their amino acid sequences, are mutually exclusive in a given SWI/SNF complex displaying distinct expression patterns and functions in humans (Oh et al 2008;Puri and Mercola 2012;Jordan et al 2013;Watanabe et al 2014). BAF60c for example, is specifically required for the transcription of myogenic-specific genes and, consequently, muscle differentiation (Forcales et al 2012).…”
mentioning
confidence: 99%